Evaluasi Resiko Keselamatan Kerja Pada Area Produksi Menggunakan Metode Hirarc di PT. Mitrametal Perkasa - Muhammad Fauzan; Andung Jati Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Occupational safety and health (OSH) is an important aspect of manufacturing activities because it is directly related to worker safety and the continuity of production processes. PT Mitrametal Perkasa, as an automotive component manufacturing company, has various work activities in the production area that potentially cause occupational accident risks, particularly in the Machining Department. Therefore, a systematic evaluation of occupational safety risks is required. This study aims to identify potential hazards, assess risk levels, and formulate occupational safety risk control measures in the production area of PT Mitrametal Perkasa. The method used in this study is HIRARC (Hazard Identification, Risk Assessment, and Risk Control). Data collection was carried out through direct observation, interviews with operators and production supervisors, and documentation studies. Risk assessment was conducted based on the likelihood and severity levels of hazards in each work activity. The results show that there are potential hazards with moderate to high risk levels, especially in CNC machine operation, handling of sharp materials, and clamping systems. Recommended control measures include the implementation of engineering controls, enforcement of work procedures, improvement of OSH training, and consistent use of personal protective equipment.